THE LEVEL OF KNOWLEDGE AND ATTITUDES OF MOTHERS IN COMPLEMENTARY FEEDING TO INFANTS AGED 0-12 MONTHS - Riesmiyatiningdyah Riesmiyatiningdyah; Kusuma Wijaya Ridi Putra; Faida Annisa; Meli Diana (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2020)
Background: Until now, there are still many mothers who give complementary foods to babies before the age of 6 months. This is due to the lack of knowledge of mothers about complementary foods, the benefits and methods of giving complementary foods correctly, and improper complementary feeding habits, as well as the support from families in providing complementary foods. These conditions affect the mother's attitude in giving complementary foods (Sulistijani & Herlianty, 2001). Objective: This study aimed to determine the relationship between the level of knowledge and attitudes of mothers in providing complementary foods to infants aged 0-12 months. Methods: The research design used correlational analytic with cross sectional approach. The population in this study were all mothers who had children aged 0-12 months in Balonggabus Village as many as 58 people. The sampling technique used was total sampling. The sample size in this study were 58 respondents. Data collection was obtained through demographic data and questionnaire sheets with a total of 26 questions. Data were analyzed using the Spearmen Rho test with a significance level of p ≤ 0.05. Results: The results showed that the level of knowledge of mothers in giving complementary foods to infants aged 0-12 months in Balonggabus Village, Candi, Sidoarjo, almost half of them had a low level of knowledge of 28 respondents (48.3%), and attitudes of mothers in giving complementary foods to babies. Most of those aged 0-12 months had negative attitudes as many as 38 respondents (65.5%). The results of statistical tests show that there is a relationship between the level of knowledge and attitudes of mothers in providing complementary foods to babies aged 0-12 months in Balonggabus Village, Candi, Sidoarjo with a significance level of 0.000 (ρ ≤ 0.05). Discussion: Based on the results of the study, it was found that the better the level of knowledge of a mother regarding complementary feeding, the mother has a positive attitude in complementary feeding. Conclusion: The implication of this study shows that the level of knowledge of mothers in providing complementary foods needs to be improved by providing information by health workers and health cadres about complementary feeding, so that the mother's attitude will be positive.